Carbon materials with controlled edge structures. (October 2017) - Yamada, Yasuhiro; Gohda, Syun; Abe, Kouki; Togo, Takaaki; Shimano, Norimichi; Sasaki, Tatsuya; Tanaka, Haruki; Ono, Hironobu; Ohba, Tomonori; Kubo, Shingo; Ohkubo, Takahiro; Sato, Satoshi
Abstract: Edges of carbon materials have been known to work as active sites for various applications such as catalysts, adsorbent, and electrodes, but selecting precursors for carbon materials with controlled edges in the absence of metallic substrate is challenging. This work developed a method to select the superior precursors instantaneously using molecular dynamic simulation. This simulation predicted that hydrogen in precursors gasified and the hydrogen attacked the active sites in precursors upon carbonization, causing the decrement of active sites. Thus, it is essential to reduce the concentration of hydrogen in precursors and it is also necessary to introduce reactive functional groups near the active site to protect the active sites. We indeed synthesized the selected precursors such as diethynyl anthracene, diethynyl chrysene, divinyl naphthyridine, and divinyl phenanthroline and proved that edges in those precursors were maintained even after carbonization at 773 K using diffuse reflectance infrared Fourier transform and X-ray photoelectron spectroscopy with the aid of spectra simulated by density functional theory calculation. Especially, ca. 100% of edge structures of zigzag edges and armchair edges in diethynyl anthracene and diethynyl chrysene was maintained even after carbonization at 773 K. Graphical abstract: